Brazilian Young Offenders: Profile and Risk Factors for Criminal Behavior - Gallo, Alex Eduardo (International Journal of Criminology and Sociology, 2013)
This paper presents a study that belongs to a research program, driving at the development of adequate social repertoire, which could decrease offences by youth. Adolescents attended in community services and probation programs in a mid-size Brazilian city were characterized, under objective of assessing the major number of variables and its correlation to criminal behavior. Data were collected in a survey design and major results showed that: 87.8% were male, and age average was 15.9 years; about the offences, theft was the most common one (36.7%) followed by robbery (15.4%) and drug-dealing (9%). Most of themwere not attending school and 61.8% had only the elementary degree. The results suggest that not attending school was associated to increasing number of re-incidences, use of drugs and use of weapons.